CURATING MEMORIES: THE ROLE OF EMOTION IN THE DIGITAL MEMORY WORK OF YOUNG WOMEN ON INSTAGRAM & FACEBOOK - Annabell, Taylor (AoIR Selected Papers of Internet Research, 2020)
A core understanding in memory studies is that memory is not formed by an individual in insolation. Instead, it is guided by social frameworks and enacted within a particular social context. This is articulated by van Dijck (2007) as an inseparability of mediated memories from culture. Accordingly, the active, purposeful creation of and re-engagement with digital traces of the past in the present on Instagram and Facebook by young women can be situated in the postfeminist, neoliberal environment. Significantly, the particular expectations and pressures on how young women should feel and act intersect with the performance of digital memory work. The purpose of this paper is to investigate the particular ‘feeling rules’ (Kanai, 2019) articulated by the young women and consider more broadly the role that emotion plays in shaping the performance of digital memory work on Instagram and Facebook. I draw on data gathered from semi-structured interviews with young women aged between 18 and 21 living in London, and ethnographic observations of their Instagram and Facebook profiles. This is complemented with a socioeconomic platform analysis (van Dijck, 2013) and a technical walkthrough (Light et al. 2016), carried out to examine how Instagram and Facebook encourage particular emotions to be expressed and the entanglement of memory and emotion in their memory product. The analysis explores the overlap between the encouragement by platforms and expectations of the postfeminist environment for happy moments to be shared with the way that different emotions influence what is shared by participants.